A reduced model to simulate the damage in composite laminates under low velocity impact. (1st April 2018) - Metoui, S.; Pruliere, E.; Ammar, A.; Dau, F.
Highlights: An algorithm based on the PGD is proposed to simulate the dynamical response of composite structure with a reduced number of degrees of freedom. The displacement, velocity and acceleration are approximated using an in-plane/out-of-plane separated representation. Cohesive zone elements compatible with the separated representation are implemented to model damage in composite laminates. The algorithm is applied to simulate a low velocity impact on a composite plate with promising results. Abstract: This article presents an efficient numerical strategy to simulate the damage in composite laminates under low velocity impact. The proposed method is based on a separated representation of the solution in the context of the Proper Generalized Decomposition (PGD). This representation leads to an important reduction of the number of degrees of freedom. In addition to the PGD, the main ingredients of the model are the following: (a) cohesive zone models (CZM) to represent the delamination and the matrix cracking, (b) a modified nonlinear Hertzian contact law to calculate the impact force, (c) the implicit Newmark integration scheme to compute the evolution of the solution during the impact. The method is applied to simulate an impact on a laminated plate. The results are similar to the solution obtained with a classical finite element simulation. The shape of the delaminated area is found to be coherent with some experimental results from the literature.